REALITAS SOSIAL AKTIVITAS MENGEMIS DAN RELEVANSINYA DENGAN IPS - Prasetyo Adi Nugroho; Nindya Nurdianasari; Trapsila Siwi Hutami (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2023)
The purpose of this study is to analyze the social reality of begging activities, both subjective reality and objective reality, and to analyze the relevance of the social reality of begging activities and social studies. Considering (1) indications of the ineffective handling problem of beggars, so does not decrease, besides the perception that begging is work; (2) many students do not understand that the concepts they learn have relevance to social life and environment. The research method used is qualitative. Data collection techniques using observation, interviews, documentation, and literature study. Data analysis techniques refer to Miles and Huberman (1992), namely, data collection; data reduction; presentation; data clarification; conclusion, and verification. The results showed, (1) the subjective reality of begging has meaning as an act of working to earn money and meet needs. While the objective reality of begging activities has meaning, begging is not a good job because it is not in accordance with social values and beggars tend to manipulate poverty, and begging is a natural act carried out by people who are lazy and people who do not have the capability to work; (2) The begging activity has relevance to social studies competence, namely identifying social interaction in space and its influence on social, economic and cultural life in terms of values and norms as well as sociocultural institutions. The actual step to realizing its relevance is to develop the basic concepts of social studies and begging, placing begging activities as a learning starting point and problems that students must solve, and formulating learning objectives and assignments describing the required student participation.Keywords: Begging, Starting Point, Student Participation